Increased γ-glutamyl transferase positively contributed to the poor prognosis in lung cancer patients - Ran, Jing Jing; He, Ruixin; Yu, Qiang; Kang, Limei; Fu, Yaoqi; Bo, Cong; Zhang, Li (Translational Cancer Research, 2018)
Background: γ-glutamyl transferase (GGT) has a critical effect on tumor initiation, progression, and metastasis; however, the particular role of circulating GGT factor in the prognosis of lung cancer remains undetermined. The aim of this study is to identify the relationship between the circulating level of GGT and poor prognosis of lung cancer patients. Methods: A total of 1,098 lung cancer patients whose GGT values were available were enrolled in this study and divided into positive and negative groups. SPSS 19.0 was introduced to analyze the relationship between GGT and clinical characteristics and metastasis. The relationship between survival status and GGT was completed by Kaplan-Meier method. Cox regression model was conducted to confirm whether GGT served as an independent risk factor in the prognosis of lung cancer. Results: Elevated GGT level was positively related to liver (P